Plan de Marketing para la Panadería y Pastelería “ANISPAN” de la Ciudad de Loja - Jaramillo Jaramillo, Gladys Elizabeth (2017)
It is estimated that in the urban sector of the city of Loja there are between two and up to three bakeries per block which has caused sales to decline due to unfair competition faced by bakeries; On the other hand there is the increase of the raw material such as wheat flour, yeast, butter and other products needed for the bread making, which leads to the product to obtain an added value. The problems that most present themselves in the bakeries of the city of Loja is the lack of training to the personnel that integrate the company, the same ones that will be very important to provide a good product and service to the citizens In society it has been seen that the food industries specifically bakeries, people are already accustomed to find the same variety and do not mind buying them, because they do not present a novel product, in addition customers always seek to taste their palate with things of Their pleasure but in many cases they do not find what they are looking for. It is for all this that a marketing plan must be carried out to solve the problem that is present within the company "ANISPAN" and thus be able to contribute to be one of the leading companies in the market of the city of Loja and also contribute with The good service to society. The main objective of the market study was to propose a marketing plan for the "ANISPAN" bakery of the city of Loja with the following analyzes. A market study was conducted to find out the percentage of acceptance of the product offered by the bakery to local families in terms of tastes and preferences, with 90% of potential consumers who are satisfied with the processed product. Then an external analysis was carried out with the political, economic, social, technological, ecological and competitive factors where a search of information of each one of the existing variables in each factor was carried out and the evolution that has had in the country each of them , Allowing to discover the opportunities and threats surrounding the bakery with which a MEFE matrix was developed, with a score of 3.42 indicating that the opportunities are being taken advantage of and facing the threats. A sector analysis was carried out, where the main competitors of the bakery were interviewed, where an analysis of the five 5 forces of Porter was carried out, and then the matrix of the competitive profile where the bakery and bakery "ANISPAN" A 3.22 positioning the market of the bakery sector. Following the internal analysis, interviews were conducted with the necessary tools to gather information about marketing and for the value chain, collecting information about the bakery, the main informants being the owner of the bakery, the accountant, and the area Of marketing, where the necessary information was found to be able to elaborate the matrix MEFI, composed by strengths and weaknesses with a total weight of 3.34 where it indicates that the bakery has reinforced strengths both in good reception that the product has, on the other Side on the weaknesses in which it is necessary to be aware of the changes that are made both in the clients and in the competition to improve and to satisfy the new needs of the local families. After all the studies carried out for the elaboration of the marketing plan with the sole aim of improving the bakery, with the help of objectives proposed for the year 2017 that will help the organizational improvement of the Bakery and Pastry "ANISPAN" of the city of Loja